Improvisation and Freedom - Bakan, Joel (Critical Studies in Improvisation / Études critiques en improvisation, 2025)
This essay, dedicated to Ajay Heble, explores how improvisation relates to two current and synergistic threats to democracy and justice: neoliberalism and illiberalism. It also examines embracing relational freedom as a method of working beyond these threats in our society.